No Zeitenwende (yet): Early Assessment of German Public Opinion Toward Foreign and Defense Policy After Russia's Invasion of Ukraine - Matthias Mader; Harald Schoen (Politische Vierteljahresschrift, 2023)
This paper addresses the question of whether Russia's invasion of Ukraine led to a~turning point ( Zeitenwende ) in public opinion on foreign and defense policy in Germany. To this end, we provide a~theoretical analysis of how the concept of turning point can be applied to public opinion. We identify the durability of the change in attitudes as well as its significance as necessary conditions to speak of a~turning point. In the remainder of the paper, we focus on the argument that changes in different types of orientations are significant to different degrees. Change in core postures is more significant than change in policy attitudes; change in attitudes thematically distant from the Russian invasion is more significant than change in attitudes directly related to the event. Empirically, we present a~panel data analysis of attitude change triggered by the Russian invasion. Analysis of data from several waves of the German Longitudinal Election Study (GLES) panel survey collected before the invasion (2017–2021) and in two waves after (May and October 2022) shows that there were sizable shifts in policy attitudes directly related to the event. Postures remained essentially unchanged, as did thematically distant attitudes. We conclude that there has been no turning point at the level of public opinion (yet).
Keywords: 320; Russo-Ukraine war; Turning point; Stability and change; Core postures; Policy attitudes; Survey data; Russisch-Ukrainischer Krieg; Stabilität und Wandel; Grundhaltungen; Sachfrageorientierungen; Umfragedaten